Persistently Biased: The Devil Shift in Water Privatization in Jakarta. Issue 5 (September 2015) - Leong, Ching
Abstract This article operationalizes an underinvestigated element of the Advocacy Coalition Framework—the "devil shift"—on the controversial issue of water privatization. In doing so, it offers a methodological premise for investigating intractable opposition to policies that are politically salient and high in technical content. It uses the Q methodology on the case of Jakarta, Indonesia to uncover seven discourse coalitions within the anti‐privatization groups. They confirm two key hypotheses within the devil shift, namely the underestimation of a coalition's resources compared with their opponents and the exaggeration of opponents' unreasonableness. Intriguingly, it finds that the "devil" is constructed in three different ways by this coalition—the profiteer, the Goliath, and the ineffectual governor. The narrative strength of the combination of these beliefs answers an apparent paradox in the devil shift viz that of rational actors persisting in unreasonable beliefs concerning their opponents. It also offers some specific solutions on how to deal with public hostility in water privatization in Jakarta.